Social Media for Consumers and Value Creation Companies - Anka Muraz (International Journal of Science and Society, 2020)
In the mid-2000s, a new marketing strategy that emerged as a result of digitization created online visibility for many companies. While many companies communicate via email, companies such as Amazon are starting to post negative comments from customers on evaluation sites. The innovations brought by digitalization began to bring new insights into marketing, but few people paid attention to these innovations. When Facebook opened its doors to the general public in 2006, the power of social media started to influence consumers and businesses, and this situation continues at its latest pace. In the summer of 2013, the three sites with the highest traffic were Facebook, Google and YouTube - either live social networking sites or platforms with strong social networking elements. Although the site is not available to those under 13 and denied access in China, the world's most populous country, one in seven people in the world is currently an active Facebook member. This striking growth of social media is only just beginning to understand business processes and models by marketing managers and researchers. It influenced the way they started. One wayTo model the radical change social media is animating is the pinball analogy, which suggests that marketing in a social media environment resembles a game of pinball, a chaotic and interactive game that replaces the bowling approach, a linear and one-way approach to marketing . As well as revealing new ways of thinking, the pin-table analogy also describes how value creation processes and structures can adapt to new marketing environments if companies are to be perceived as profitable by active, highly connected consumers via networks. In this study, while presenting an overview of the new environment, it also deals with important reflections on marketing managers and companies exposed to this enlightenment.